What’s new in the Visionaire system® in second-generation for TKA? a comparative study of accuracy, efficiency and functional results - Fontes, Ana Paula; Cintra, Rui Miguel; Gomes, Luis; Sousa, Joao Paulo (International Journal of Research in Orthopaedics, 2022)
Background: The aim of the study was to analyze and compare the accuracy, efficiency and functional evolution between the first- and second-generation Patient-specific instrumentation (PSI). Methods: We report our experience in TKA using PSI Visionaire System® (Smith and Nephew®) in 456 procedures. The patients were divided into first- (N=272) and second-generation PSI design (N=184). For the accuracy was analyzed the mechanical results, namely Hip-knee-ankle (HKA) alignment post-TKA and outliers’ frequency; for the efficiency was analyzed the length time surgery, the length of stay and satisfaction, for the functional outcomes was compared the evolution at pain, range of motion, gait perimeter and the domains of the Western ontario and mcmaster osteoarthritis index (WOMAC). The t-test for independent samples was applied in the continuous numeric variables and Qui square tests in the dichotomic nominal variables. Statistical significance was p value<0.05. Results: The alignment of the femur worsened significantly in the second-generation (p=0.002), but the alignment of the tibia was improved (p=0.010). However, not enough to improve significantly the HKA. No significant differences were observed in the frequency of outliers. The length of stay decreased in the second-generation (<0.001). The functioning achieved at first and third months after surgery was lower in second-generation PSI; at first month in the pain and stiffness WOMAC (p=0.030; p>0.001) and in the third in WOMAC stiffness (p<0.001). Conclusions: The second-generation PSI of Visionaire system® improved the alignment of the tibia, but not the alignment of the femur. This change did not produce any improvements in functioning.